English pronunciation in use : - Hancock, Mark (Cambridge University Press, 2007)
The best-selling English Pronunciation in Use is a comprehensive reference and practice book suitable for self-study or classroom work. Fifty easy-to-use units cover all aspects of pronunciation, including individual sounds, word stress, connected speech and intonation. An additional reference section offers a glossary of specialized terms, help with the pronunciation of numbers and geographical names and fun exercises on phonemic symbols and minimal pairs.